Family Financial Resilience Efforts Through Financial Management Training in Bangah Sidoarjo Village - Ladi Wajuba Perdini Fisabilillah; Tony Seno Aji; Mohammad Wasil; Aprillia Nilasari; Aminudin Ma’ruf; A’imatul Mustafidah; Moh Ashra Faishal Mabani (International Journal Of Community Service, 2025)
Global economic instability triggered by the COVID-19 pandemic, geopolitical conflicts, inflation, and commodity price fluctuations has increased household financial vulnerability in Indonesia, especially among low- and middle-income groups. Many households, particularly those led by housewives, lack adequate financial literacy and skills in managing household budgets. This community service program aimed to enhance family financial resilience by educating housewives in Bangah Village, Sidoarjo, on healthy household financial management. The activity, held on July 20, 2025, involved 70 participants and was implemented through three stages: education using interactive presentations, practical exercises through case studies, and evaluation via pre- and post-tests. The pretest revealed that 70% of participants had not managed household finances effectively. Post-test results indicated a 20% improvement, with 90% of participants understanding proper budget allocation and distinguishing needs from wants. The program successfully increased participants’ knowledge and skills in managing finances, though some still reported expenditures exceeding income. Participants suggested future training include topics on investment and digital literacy.